Comparative analysis of endocrown fracture resistance and marginal adaptation: CAD/CAM technology using lithium disilicate vs. zirconia-reinforced lithium silicate ceramics - Ezatollah Jalalian; Arash Zarbakhsh; Sotude Khorshidi; Shaghayegh Golalipour; Sara Mohammadnasl; Maryam Sayyari (Elsevier, 2024)
Aims: The present study aimed to compare the fracture resistance and marginal adaptation of endocrowns fabricated using lithium disilicate (LDS) and zirconia-reinforced lithium silicate 9ZLS) ceramics by the computer-aided design and computer-aided manufacturing (CAD/CAM) technology. Materials and Methods: In this in vitro experimental study, 24 extracted mandibular first molars received standard endocrown preparation and were randomly assigned to two groups (n = 12) for the fabrication of endocrowns with ZLS (Suprinity) and LDS (IPS e.max CAD) ceramics. After scanning the teeth with a CAD scanner, endocrowns were designed by inLab Software version 15 (inLab SW 15) and prepared by an imes-icore 350i milling machine. The vertical marginal gap of endocrowns was measured under a stereomicroscope at three steps before and after cementation and after thermomechanical cycles. The fracture resistance of specimens was then measured by load application at a 45° angle. Mode of failure was also determined as reparable or irreparable. Data were analyzed using Pearson's correlation test and t-test. Results: The mean fracture resistance of ZLS endocrowns was significantly higher than that of LDS endocrowns (P = 0.000). The reparability of ZLS endocrowns was zero, while that of LDS endocrowns was 83.33 %. The vertical marginal gap was significantly smaller in ZLS than in LDS endocrowns at all three time points (P < 0.05). Also, the marginal gap increased by cementation and thermomechanical cycles in both groups. Conclusion: ZLS and LDS endocrowns both showed acceptable vertical marginal adaptation. ZLS had superior marginal adaptation and higher fracture resistance.